High removal of phosphate from wastewater using silica sulfate - Jutidamrongphan, W.; Park, K. Y.; Dockko, S.; Choi, J. W.; Lee, S. H. (SPRINGER HEIDELBERG, 2012)
This report shows that silica sulfate is removing phosphate from wastewater very efficiently. Phosphorus removal and recovery from wastewater is a worldwide issue due to pollution of natural waters by phosphate and depletion of phosphate ores. Adsorption is a process that can remove phosphate at low concentrations. Adsorption also allows the recovery of phosphate for possible re-use. Here, we studied the adsorption of phosphate from wastewater using commercial Zr ferrite, Zr-MCM 41 and silica sulfate. We calculated equilibrium isotherms, kinetic models and thermodynamic effects under conditions similar to real wastewaters. We found that the equilibrium data for the adsorption of phosphate were best fitted to the Freundlich model. The results show that the maximum uptake of phosphate was 3.36 mg g(-1) for Zr-MCM, 27.73 mg g(-1) for Zr ferrite and 46.32 mg g(-1) for silica sulfate. The kinetic results of the three adsorbents were satisfactorily predicted using a pseudo-second-order model. We found that silica sulfate provided excellent characteristics in terms of the maximum adsorption and rate constant for the adsorption of phosphate. The thermodynamic data showed that increasing the temperature enhanced the adsorption of phosphate onto silica sulfate. Our findings will help to define efficient methods to remove phosphate from wastewater.